Effect Of Different Sintering Temperatures on the Mechanical Properties of Porcelain - Zulkifli, Mohd Azmi; Mohd, Norhayati (Tropical Scientific Journal, 2026)
Objective: This study investigates the effect of different sintering temperatures on the mechanical properties of porcelain, with particular attention to modulus of rupture and microhardness. The main objective of this research is to determine how varying sintering temperatures (800°C, 900°C, 1000°C, and 1100°C) influence these mechanical properties and to identify the optimal temperature conditions for achieving maximum strength and hardness. Research Method: Porcelain slip obtained from Claytan, with a specific gravity of 1.8, was poured into molds, dried, and sintered at four different temperatures. The sintered samples were tested for modulus of rupture using a standard bending test and for microhardness using a Mitutoyo Vickers hardness tester under a load of 0.5 kg. Findings: The results indicate that the modulus of rupture increases steadily with rising temperature, reaching its highest value at 1100°C, which demonstrates that this temperature promotes optimal densification and bonding. In contrast, the microhardness results reveal a different trend, with the highest hardness achieved at 1000°C, followed by a slight decrease at 1100°C. This reduction may be attributed to grain coarsening or excessive vitrification that weakens resistance to localized deformation. Overall, the findings confirm that sintering temperature has a direct and significant impact on the mechanical performance of porcelain. Originality: The originality of this study lies in identifying 1000°C as the most effective temperature for enhancing hardness and 1100°C as the optimal temperature for maximizing flexural strength